Development of BSP for ARM9 Evaluation Board - Vinayak Pandit K.; Sanket Dessai; Shilpa Chaudhari (Institute of Advanced Engineering and Science, 2015)
With an increasing usage of ARM9 core for different kinds of applications ranging from data acquisition to Mobile application, there arises the need for developing ARM9 based board. To bring up this board, board supporting package (BSP) is must. Board supporting package virtualizes the platform hardware so that the different drivers can be ported easily on any hardware. The boot loader is the initial stage of firmware, which initializes the hardware components presents on the board. A universal Bootloader is chosen and is to be customized with respect to target board. In the later section bootloader is interfaced to the kernel which is obtained form an authorized distributor under general purpose license. The customized board specific routines as well drivers are ported onto the hardware. Then the compiled kernel image is ported onto the target board using a debugger and SAM-BA utility. Linux kernel has seen major releases; the basic architecture of the Linux kernel has remained more or less unchanged. The latest 2.6 version of Linux kernel is ported onto target hardware. Kernel support for many architectures and high-end I/O devices gives the independence to choose appropriate hardware for developing system. The bootloader customization is the critical step, which involves a lot of modifications in the header files. BSP components such as bootloader, kernel is compiled using GNU tool chain; obtained image is ported on target using debugger. BSP porting is a very complex task, which required knowledge of hardware and software control sequence and boot strategy of the controller.